MORFOLOGI DAN KLASIFIKASI TANAH PADA BERBAGAI MACAM SUB-LANDFORM KARST DI FORMASI WONOSARI KECAMATAN GEDANGAN, KABUPATEN MALANG - Andre E S Sitinjak; Mochtar Lutfi Rayes; Christanti Agustina (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Limestone materials in Wonosari formation produces karst landform through the karstification processes. The different type of karst landform can affect soil morphology and soil classification. This research was conducted in Gedangan District, Malang Regency, East Java Province, Indonesia. Soil morphology identified at 54 minipits to know the range of soil characteristics, continued with detailed survey on 6 typical pedons to detailed soil classification. Soil samples were taken at each horizon for analyses of soil physical and chemical properties. Soil morphology at study area has very dark brown (7.5YR2.5/2) to yellowish brown (10YR5/8) soil colours, silty clay loam to silty clay textures, subangular blocky, fine, weak to moderate structures, very friable to very firm, sticky to very sticky, slightly plastic to plastic consistencies. There are no rock fragments at hilly and valley karst and shallow soil depth in hilly than in valley karst. Soil classification differs at each sub landform, i.e. top hilly karst is classified as Lithic hapludolls, fine, mixed, isohyperthermic, hilly karst classified as Typic calciudolls, fine, calcareous, superactive, isohyperthermic, Typic hapludolls, fine, mixed, superactive, isohyperthermic, plateau karst classified as Inceptic haprendolls, skeletal-clay, mixed, superactive, isohyperthermic, valley karst classified as Eutric humudepts, fine, mixed, superactive, isohyperthermic, and Typic humudepts, fine, mixed, superactive, isohypertermic.